A review on the application of conciliation and mediation in trade disputes in Malaysia / Nur Hannan Ishak, Nadiatul Najwa Jalaldin and Shafiqah Balqis Adnan. - Ishak, Nur Hannan; Jalaldin, Nadiatul Najwa; Adnan, Shafiqah Balqis (2011)
In Malaysia, the law which governed trade dispute is known as employment law. It consists of the Employment Act 1955, the Industrial Relations Act 1967 (IRA 1967), Trade Unions Act 1959 and Employees Social Security Act 1969. These Acts contain provisions which protect both, the employer and employee's right of employment, safeguards against unfair dismissal, Collective Agreement and social benefits. Trade dispute, according to Section 3 of the IRA 1967, means any dispute between an employer and his workmen which is connected with the employment or non-employment or the terms of employment or the conditions of work of any such workmen. Trade dispute can also be referred as industrial dispute. Industrial dispute has been defined as any dispute between workers and their own employer relating to terms and conditions of employment, the dismissal of employee, allocation of duties between employees, disciplinary matters and so on. Another term used which is similar with "trade dispute" and "industrial dispute" is labour dispute. Labour disputes are controversies between an employer and its employees concerning the terms or conditions of employment, or concerning the association or representation of those who negotiate or seek to negotiate the terms or conditions of employment. Industrial conflict is defined as the conflict between the employer and the employee generally.